Novel Near-Field Microwave Testing Method for Outdoor Insulators - Saker, Yasser Adel (2011)
A Master of Science thesis in Electrical Engineering submitted by Yasser Adel Saker entitled, "Novel Near-Field Microwave Testing Method for Outdoor Insulators," June 2011. Available are both soft and hard copies of the thesis.